2017
DOI: 10.2147/rru.s135375
|View full text |Cite
|
Sign up to set email alerts
|

Does intraperitoneal injection of propofol prior to detorsion improve testes weight and histopathological findings in a rat model?

Abstract: ObjectivesTo determine the long-term preventive effects of intraperitoneal propofol on testicular ischemia–reperfusion injury in a rat model.Materials and methodsForty adult male albino Wistar rats were divided randomly into the following four groups according to the planned treatment (n=10 per group): group I, control; group II, sham-operated; group III, torsion/detorsion (T/D); and group IV, T/D plus propofol. Testicular ischemia was achieved by twisting the left testis 720° clockwise (ie, applying torsion) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…These irreversible changes may be related to subsequent declines in fertility [20]. Although the mechanism of testicular tissue injury during torsion is not fully understood, studies so far have shown that the main pathophysiological event is I/R injury [21,22]. The role of autophagy in testicular I/R injury is supported by reports on improved autophagy in Kidney injury, such as I/R injury [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…These irreversible changes may be related to subsequent declines in fertility [20]. Although the mechanism of testicular tissue injury during torsion is not fully understood, studies so far have shown that the main pathophysiological event is I/R injury [21,22]. The role of autophagy in testicular I/R injury is supported by reports on improved autophagy in Kidney injury, such as I/R injury [23,24].…”
Section: Discussionmentioning
confidence: 98%